Evaluating fishing techniques and sustainability status of spanish mackerel (Scomberomorus sp.) under an ecosystem-based fisheries management framework - Sinaga, Merry Friendly Theresia; Prianto, Eko; Fauzi, Muhammad (Journal of Earth Kingdom, 2026)
Background: Spanish mackerel (Scomberomorus sp.) is one of the high-value fishery commodities that is widely harvested in the Terubuk Fishery Reserve Area, Buruk Bakul Village. The increasing demand and market price of Spanish mackerel have led to high fishing intensity, which may exert pressure on the resource stock. The fishing techniques employed in the mackerel fishery play a critical role in ensuring the sustainability of this resource. This study aims to evaluate the status of Spanish mackerel fishing techniques within the framework of the Ecosystem Approach to Fisheries Management (EAFM). Methods: Data collection was carried out through surveys and interviews with fishers during the period of November–December 2024 in Buruk Bakul Village, Bengkalis Regency. The analysis applied a multi-criteria method using a flag model, which assessed indicators such as destructive fishing practices, gear modification and auxiliary devices, fishing capacity and effort, selectivity of gear, and the compliance of vessel function and size with legal documentation. Findings: The findings indicate that Spanish mackerel fishing techniques in this area fall under the “good” category, with a score of 220. These results indicate that the management of Spanish mackerel in the Terubuk Sanctuary Area, in terms of fishing techniques, remains in good condition and applies the principles of sustainable fisheries. However, several indicators require improvement. Conclusion: The study concludes that Spanish mackerel fishing practices in the Terubuk Sanctuary Area are generally sustainable and categorized as good, but improvements are still needed in fishing capacity and effort, gear selectivity, and vessel compliance. Optimizing these aspects will help ensure the long-term sustainability of the resource while maintaining fishery efficiency.